Cryptography in C and C++ 2nd Edition - Welschenbach, Michael (Apress, 2012)
THE SECOND AMERICAN EDITION OF this book has again been revised and enlarged. The chapter on random number generators has been completely rewritten, and the section on primality testing was substantially revised. The new results of Agrawal, Kayal, and Saxena on primality tests, whose discovery in 2002 that “PRIMES is in P” caused a sensation, are covered. The chapter on Rijndael/AES has been relocated for a better presentation, and it is pointed out that the standardization of Rijndael as the Advanced Encryption Standard has meanwhile been made official by the U.S. National Institute of Standards and Technology (NIST). Unlike previous editions of the book, the second American edition does not contain a CD-ROM with the source code for the programs presented. Instead, the source code is available for download at www.apress.com in the Downloads section.¬«¾